YouTube as a source of information on COVID-19 vaccination in rheumatic diseases - Kocyigit, Burhan Fatih; Akyol, Ahmet (SPRINGER HEIDELBERG)
As the most well-known and popular video-sharing platform around the world, YouTube is an influential tool for the dissemination of health-related information. In addition, considering the increase in obtaining information from internet-based sources in pandemic conditions, YouTube has become more important in the presentation of information related to COVID-19. Therefore, the aim of this study was to evaluate videos related to COVID-19 vaccination in rheumatic diseases (RD) on YouTube. In this descriptive study, 334 video URLs listed with six search terms were recorded (26 July 2021). Three quality groups (high, intermediate, and low) were created based on the Global Quality Scores (GQS). Video sources were identified and various video parameters were compared between the quality groups. Following the implementation of the exclusion criteria, 56 videos remained for further analysis; of which 37 (66.07%) were evaluated as high quality, 12 (21.42%) as intermediate quality, and 7 (12.51%) as low quality. No significant difference was determined between the quality groups in per day values of views, likes, dislikes, and comments. The sources of high-quality videos were pharmaceutical company (n = 1; 100%), pharmacist (n = 1; 100%), society-organization (n = 17; 85%), and academic (n = 3; 75%). Although two-thirds of the videos were high quality, it should be kept in mind that intermediate and low-quality videos are also available. Users should not assume the quality of the videos based on the number of views, likes, dislikes, and comments, but should focus more on video sources.
Keywords: YouTube; COVID-19; SARS-CoV-2; Vaccination; Vaccine; Rheumatic disease; Rheumatology